2020
DOI: 10.4067/s0718-58392020000100021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-emergence herbicides on stress indicators in quinoa

Abstract: The impact of herbicide application on the accumulation of secondary metabolites and photosynthesis as stress indicators in the quinoa (Chenopodium quinoa Willd.) crop is unknown. The objective of the present study was to evaluate the effect of two post-emergence herbicides on production, total polyphenol content, and chlorophyll fluorescence in quinoa. The experiments were conducted for two consecutive seasons using a completely randomized block design with seven treatments, including two herbicides and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Polyphenols are secondary metabolites that are essential in plants because they perform functions in response to stress conditions (Merino et al, 2020). Whereas DPPH-free radical scavenging is an indicator of non-enzymatic antioxidant activity.…”
Section: Phenolic Compounds and Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols are secondary metabolites that are essential in plants because they perform functions in response to stress conditions (Merino et al, 2020). Whereas DPPH-free radical scavenging is an indicator of non-enzymatic antioxidant activity.…”
Section: Phenolic Compounds and Antioxidant Activitymentioning
confidence: 99%
“…Reduced crop growth and yield can be influenced by a decline in photosynthesis (Ali and Honermeier, 2016); however, this stress can diminish the biomass production, alter the quantity of the secondary plant metabolites (Olivoto et al, 2016); and increase the polyphenol content of the tissues (De Abreu and Mazzafera, 2005). Although, Merino et al (2020) stated that the total polyphenol content did not change duo to the herbicide application regardless the effect on the quinoa yield.…”
Section: Phenolic Compounds and Antioxidant Activitymentioning
confidence: 99%
“…Jacobsen et al demonstrated that inter-row hoeing with a 50 cm distance can significantly reduce weeds in quinoa fields [3], but this traditional method is inefficient when dealing with large quinoa fields. Weeds such as grasses and broadleaf species are difficult to eradicate completely, and therefore affect the normal growth of quinoa [4]. Manual weeding is labor-intensive and costly, and it is often abandoned in the later stages, which then severely affect the yield and quality of the quinoa [5].…”
Section: Introductionmentioning
confidence: 99%
“…POST herbicides are necessary for nut sedge control, nonetheless few herbicides can be safely used pre or post transplant in tomato cultivation (Manning and Fennimore, 2001;Boyd, 2016;Merino et al, 2020). For this reason, most farmers apply PRE transplanting herbicides such as metribuzin and (S)-metolachlor (Devkota et al, 2013), and POST transplanting herbicides such as halosulfuron (Haar et al, 2002) for nut sedge suppression (Freeman et al, 2016;Boyd and Dittmar, 2018).…”
Section: Introductionmentioning
confidence: 99%